Phosphorylation timers in the 'neurospora crassa' circadian clock - Diernfellner, Axel; Brunner, Michael (Journal of molecular biology, 2020)
Circadian clocks are self-sustained oscillators that orchestrate metabolism and physiology in synchrony with the 24-hday-night cycle. They are temperature compensated over a wide range and entrained by daily recurring environmental cues. Eukaryotic circadian clocks are governed by cell-based transcriptional-translational feedback loops (TTFLs). The core components of the TTFLs are largely known and their molecular interactions in many cases well established. Although the core clock components are not or only partly conserved, the molecular wiring of TTFLs is rather similar across kingdoms and phylae. In all known systems, circadian timing relies critically on casein kinase 1 (CK1) and CK1-dependent hyperphosphorylation of core clock proteins, in particular of negative elements of the TTFLs. Yet, we lack concepts as to how phosphorylation by CK1a and other kinases relates to timekeeping on the molecular level. Here we summarize what is known about phosphorylation of core components of the circadian clock of Neurospora crassa and speculate about the molecular basis of circadian timekeeping by hyperphosphorylation of intrinsically disordered regions in clock proteins.
Gesehen am 16.07.2020